2015
DOI: 10.1007/s11357-015-9765-1
|View full text |Cite
|
Sign up to set email alerts
|

Female PAPP-A knockout mice are resistant to metabolic dysfunction induced by high-fat/high-sucrose feeding at middle age

Abstract: Longevity and aging are influenced by common intracellular signals of the insulin/insulin-like growth factor (IGF)-1 pathway. Abnormally high levels of bioactive IGF-1 increase the development of various cancers and may contribute to metabolic diseases such as insulin resistance. Enhanced availability of IGF-1 is promoted by cleavage of IGF binding proteins (IGFBPs) by proteases, including the pregnancyassociated plasma protein-A (PAPPA). In vitro, PAPP-A is regulated by pro-inflammatory cytokines (PICs) such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…To understand the effects of IGF-1 deficiency on the cerebral microcirculation in the present study, we used a novel mouse model of adult-onset isolated endocrine IGF-1 deficiency, which phenotypically better mimics age-related IGF-1 deficiency observed in humans that most other available rodent models of GH/IGF-1 deficiency (Arum et al 2014a;Hill et al 2015;Rojanathammanee et al 2014;Wiesenborn et al 2014;Arum et al 2014b;Schneider et al 2014). Serum IGF-1 levels and physiological parameters obtained in the same experimental cohorts of animals used for the present study have been recently reported (Toth et al 2014a).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the effects of IGF-1 deficiency on the cerebral microcirculation in the present study, we used a novel mouse model of adult-onset isolated endocrine IGF-1 deficiency, which phenotypically better mimics age-related IGF-1 deficiency observed in humans that most other available rodent models of GH/IGF-1 deficiency (Arum et al 2014a;Hill et al 2015;Rojanathammanee et al 2014;Wiesenborn et al 2014;Arum et al 2014b;Schneider et al 2014). Serum IGF-1 levels and physiological parameters obtained in the same experimental cohorts of animals used for the present study have been recently reported (Toth et al 2014a).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of local, tissue-specific IGF-1 expression and activity is important in deciphering the phenotypic consequences of altered GH signaling, including its effects on healthspan and lifespan. Studies in animals with deletion of pregnancy associated plasma A (PAPP-A), a protease that degrades IGF-1 binding proteins, provided important evidence for the role of local (tissue) availability of biologically active IGF-1 in the control of aging and longevity [129, 130]. …”
Section: Insulin-like Growth Factor 1 (Igf-1) and Agingmentioning
confidence: 99%
“…Mice in which CNOT6 has been deleted are viable but, with exception of some bone abnormalities, do not have obvious changes in phenotype. However, CNOT3 heterozygous mice (Morita et al ., 2011) display some phenotypes reminiscent of Snell (Bartke & Brown‐Borg, 2004; Boylston et al ., 2006), Ames dwarf (Boylston et al ., 2006), GHRKO (Brown‐Borg & Bartke, 2012), and PAPPA‐KO mice (Hill et al ., 2015), including higher insulin sensitivity, improved glucose tolerance, and higher oxygen consumption. Here, we present evidence suggesting that Snell, GHRKO, and PAPPA‐KO mice express high levels of NDRG1 and MGMT proteins that are under the control of mTORC1 activity, and that this regulation involves post‐transcriptional mechanisms that may depend on alteration of the CCR4‐NOT complex.…”
Section: Introductionmentioning
confidence: 99%